A Selective and Sensitive Phenanthroimidazole‐Based "Reactive" Ratiometric Sensor for Recognition of Hg2+ Ions in Aqueous Solution. Issue 12 (31st October 2014) - Yan, Yuanyuan; Zhang, Rui; Yu, Xiang; Xu, Hui
Abstract Based on specific reactivity of the vinyloxy group to Hg2+ ions, a new ratiometric phenanthroimidazole‐based fluorescent sensor, 2‐(2‐(vinyloxy)phenyl)‐1 H‐phenanthro[9, 10‐d]imidazole, is prepared. The selectivity of the probe toward Hg2+ ions is very high, and shows minimal interference from other commonly coexistent metal ions. The reactive stoichiometry of the probe with Hg2+ ion is 2:1. Its detection limit is evaluated and Hg2+ ions can be detected down to a lower limit of 2.5×10−8 M. Moreover, the Hg2+‐promoted selective hydrolysis of a vinyloxy group of the probe is further confirmed by 1H NMR spectroscopy and mass spectrometry.